Concerns and professional development needs of faculty at King Saud University in Saudi Arabia in adopting online teaching - Omar, Saud (Kansas State University, 2016)
With the number of students at King Saud University exceeding 60,000, the university faces a need to adopt online teaching. The purpose of this study was to investigate the concerns of the faculty in the nine departments of the College of Education at King Saud University regarding the adoption of online teaching and to relate their concerns to their professional development needs. The Concerns-Based Adoption Model (CBAM) was utilized as a theoretical framework, and a non-experimental, cross-sectional survey design was used to collect the data. The data were obtained from 296 faculty members, which was a response rate of 66%. Respondents’ stages of concern 0-2 (Unconcerned, Informational, and Personal) were the highest, while stages 4-6 (Consequence, Collaboration, and Refocusing) were the lowest. The highest stage of concern was stage zero (Unconcerned), with a 96% percentile score. This indicated that respondents had little concern about or involvement with online teaching. The second highest stage score was stage one (Informational), with a 90% percentile score. This indicated that the respondents wanted more information about online teaching. Additionally, stage six (Refocusing) tailed up 15 percentile points, which indicated that respondents might be resistant to online teaching. A one-way MANOVA test result (p = .047) revealed a statistically significant difference between respondents' age and respondents' concerns in adopting online teaching. The statistical significance differences were found in stage zero (Unconcerned) (p = .041) and stage six (Refocusing) (p = .018). Another one-way MANOVA test results (p = .004) showed a statistically significant difference between respondents' gender and respondents' concerns in adopting online teaching. The statistically significance differences were found in stage zero (Unconcerned) (p = .035) and stage three (Management) (p = .001). t-test results indicated that female participants had a higher concern on both stages than male participants. Additional one-way MANOVA test results (p = .004) also indicated a statistically significant difference on the participants' concerns when adopting online teaching based on their department association. The significance value was found in stage three (Management) (p = .005). Another one-way MANOVA test showed a statistically significant difference on the concern based on the academic rank (p=.053). The significance values were found in stage one (Informational) (p = .001), stage two (Personal) (p = .002), and stage three (Management) (p = .002). Finally, three MANOVA tests indicated statistically significant differences: First, on participants' use of technology in teaching based on their prior instructional technology use (p = .017); second, on participants' use of technology in teaching based on their perception of technology-related professional development needs (p=.031); third, on participants' use of technology in teaching based on their attitudes toward online teaching (p=.004) and (p=.002). The study concluded with recommendations for future studies and for King Saud University regarding designing and implementing training programs to improve the faculty adoption of online teaching.
Keywords: Educational technology; Saudi Arabia; Professional development; Online teaching; CBAM; Higher education